2017
DOI: 10.1136/heartjnl-2016-310403
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting stents versus bare-metal stents in acute myocardial infarction with cardiogenic shock

Abstract: Despite the frequent use of DES nowadays, a substantial number of patients were treated by BMS in AMI complicated by CS. After adjustment for risk factors, the 1-year outcome of patients treated by DES compared with BMS was similar. TRIAL REGISTRATIONNUMBER: www.clinicaltrials.gov: NCT00491036.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
8
1
2
Order By: Relevance
“…174 In a recent subanalysis of the IABP-SHOCK II trial, no differences in outcomes between DES and bare metal stent were observed. 175 The outcome differences associated with complete revascularization versus culprit-only PCI remain unclear. In stable patients with STEMI undergoing primary PCI, treatment of culprit and nonculprit vessels appears to be safe and may be associated with improved outcomes.…”
Section: Pci Strategymentioning
confidence: 99%
“…174 In a recent subanalysis of the IABP-SHOCK II trial, no differences in outcomes between DES and bare metal stent were observed. 175 The outcome differences associated with complete revascularization versus culprit-only PCI remain unclear. In stable patients with STEMI undergoing primary PCI, treatment of culprit and nonculprit vessels appears to be safe and may be associated with improved outcomes.…”
Section: Pci Strategymentioning
confidence: 99%
“…However, the roles of DES and BMS are still indefinite. All the long-term causes of mortality were better in those who underwent DES implantation, while the other two were neutral in a retrospective analysis [86,87]. Still, even though using DES instead of BMS does not have any adverse effect, the use of DES is still recommended in CSMI patients.…”
Section: Types Of Revascularizationmentioning
confidence: 93%
“…In the contemporary era characterized by near universal stent implantation during PCI, the comparative effectiveness of BMS versus DES has been evaluated in a few observational studies, summarized in Table . In a cohort composed of the IABP‐SHOCK II trial and registry datasets ( n = 652), DES were associated with lower unadjusted rates of the composite of all‐cause mortality or recurrent MI at 1 year compared with BMS, but adjusted rates were similar with BMS and DES (HR: 0.83; p = .14) . In another study from a Taiwanese registry, 1,017 patients with AMICS treated with a DES were matched using propensity score to 2034 patients treated with BMS.…”
Section: Stent Selectionmentioning
confidence: 99%